2020
DOI: 10.1021/acsnano.0c05367
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Mechanical and Optoelectronic Properties of Organic Cocrystals by Unexpected Stacking Transformation from H- to J- and X-Aggregation

Abstract: Molecular stacking modes, generally classified as H-, J-, and X-aggregation, play a key role in determining the optoelectronic properties of organic crystals. However, the control of stacking transformation of a specific molecule is an unmet challenge, and a priori prediction of the performance in different stacking modes is extraordinarily difficult to achieve. In particular, the existence of hybrid stacking modes and their combined effect on physicochemical properties of molecular crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 60 publications
2
77
0
Order By: Relevance
“…Using this methodology, we have calculated to a high accuracy versus experiment the elastic constants of amino acid 90,[98][99][100] and peptide crystals, 101,102 co-crystals, 103,104 and biominerals 105 (Fig. 2).…”
Section: Elastic Properties Of Electroactive Materialsmentioning
confidence: 99%
“…Using this methodology, we have calculated to a high accuracy versus experiment the elastic constants of amino acid 90,[98][99][100] and peptide crystals, 101,102 co-crystals, 103,104 and biominerals 105 (Fig. 2).…”
Section: Elastic Properties Of Electroactive Materialsmentioning
confidence: 99%
“…In 2020, the same research group demonstrated the molecular stacking mode interactions between rigid aromatic 4,4′‐bipyridine (4,4′‐Bpy) and a nonaromatic amino acid derivative of N‐acetyl‐L‐alanine (AcA) (see Figure a). [ 85 ] Transitions between the three known types of molecular stacking modes are known, namely, H‐aggregation (face‐to‐face stacking), J‐aggregation (staggered stacking) and X‐aggregation (crossed stacking), were observed in the hybrid system (Figure 7b,c). Due to the difficulties in studying each stacking mode in single molecules, hybrid systems were selected to study their physicochemical properties.…”
Section: Organic Piezoelectric Energy Harvestersmentioning
confidence: 99%
“…Initially the methodology was benchmarked with respect to three well-known inorganic piezoelectric materials; namely aluminium nitride (AlN), zinc oxide (ZnO) and α-quartz (SiO 2 ). This was then extended to the proteinogenic amino acids (Guerin et al, 2018a), biominerals (Guerin et al, 2018b), co-crystals (Ji et al, 2020) and peptides (Bera et al, 2021), with deviations from experiment ranging from 1-20%, which is highly accurate for identifying highperformance materials. The upper limit is observed in highly flexible materials with individual stiffness constants of less than 5 GPa.…”
Section: Dielectric Tensormentioning
confidence: 99%